Semantic Peculiarities of Feminine Derivatives in the Old English Language - Yesypenko, Nadia; Soloviova, Olga (My University, 2020)
The article deals with the relationship between semantics and suffixes in Old English. It has been hypothesized that suffixes that form nouns belonging to a particular gender have certain segments of meaning that differ from those of other genders during the same period of language evolution. In order to identify such features, an analysis of feminine derivatives was conducted. The analysis of semantic segments was based on identifying twenty-one semantic segments, inherent in derivatives and their bases. Our findings show that the main semantic segments characteristic of feminine suffixes include abstractions, feelings and traits of character, names of actions and results of actions.
Keywords: Old English suffixes; gender; semantic derivation; non-recursive derivation